2023
DOI: 10.3390/ijms24087269
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Mechanisms of Melatonin on Delaying Drought-Induced Leaf Senescence in Cotton

Abstract: Leaf senescence reduces the photosynthetic capacity of leaves, thus significantly affecting the growth, development, and yield formation of cotton. Melatonin (MT) is a multipotent substance proven to delay leaf senescence. However, its potential mechanism in delaying leaf senescence induced by abiotic stress remains unclear. This study aimed to explore the effect of MT on delaying drought-induced leaf senescence in cotton seedlings and to clarify its morphological and physiological mechanisms. Drought stress u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 96 publications
4
13
0
Order By: Relevance
“…MT reduced the upregulation of ABA biosynthesis genes, NCED1 and NCED2, and their accumulation in cotton [129]. Similarly, exogenous MT delayed leaf senescence via the upregulating genes involved in IAA, GA3, and CTK biosynthesis, such as GHIPT2, GhYUC5, and GhGA3ox2, thereby increasing the endogenous levels of IAA, GA3, and indole-3-propionic acid (iPA) in different plants under drought stress [126]. ABA is a priming hormone that promotes leaf senescence in response to abiotic stress.…”
Section: Mt Relevant Genes Involve In Cotton Growthmentioning
confidence: 99%
“…MT reduced the upregulation of ABA biosynthesis genes, NCED1 and NCED2, and their accumulation in cotton [129]. Similarly, exogenous MT delayed leaf senescence via the upregulating genes involved in IAA, GA3, and CTK biosynthesis, such as GHIPT2, GhYUC5, and GhGA3ox2, thereby increasing the endogenous levels of IAA, GA3, and indole-3-propionic acid (iPA) in different plants under drought stress [126]. ABA is a priming hormone that promotes leaf senescence in response to abiotic stress.…”
Section: Mt Relevant Genes Involve In Cotton Growthmentioning
confidence: 99%
“…Previous studies have shown that a lack of water causes an increase in reactive oxygen species (ROS) production, which causes oxidative damage to chloroplast and a decrease in chlorophyll content that limits photosynthesis [4,5]. Plant hormones such as indole-3-acetic acid, ethylene, jasmonic acid, gibberellic acid, cytokinins, abscisic acid, and salicylic acid are important signals for plant growth and development [6,7], and they also play a role in plant stress response [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Stressful circumstances can modify the level 2 of 25 of endogenous hormones by regulating the biosynthesis or degradation of hormones either directly or indirectly [8,14]. Phytohormones are regarded as important endogenous molecules for regulating physiological and biochemical responses, even though the plant's response to stresses is dependent on a variety of factors [10,11]. Numerous studies have demonstrated that MT provides significant benefits for plant growth and development under stressful conditions [5,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations